THE ROLE OF TECHNOLOGY IN ENGLISH LANGUAGE LEARNING IN THE DIGITAL ERA - Hasbiyah Srianah Amir; Utary Rustam (Yayasan Adra Karima Hubbi, 2025)
The rapid advancement of technology has significantly transformed English language learning in the digital era. Traditional classroom-based learning has shifted towards technology-enhanced instruction, incorporating digital tools, mobile applications, artificial intelligence, and online learning platforms. This transformation presents new opportunities and challenges in language acquisition, necessitating an in-depth exploration of technology's role in facilitating English language learning. This study aims to analyze the impact of digital technologies on English language learning, focusing on their effectiveness in improving learners' linguistic competencies, engagement, and motivation. A qualitative research method was employed, involving a systematic literature review and thematic analysis of recent studies on technology-assisted language learning. Data were collected from peer-reviewed journal articles, conference proceedings, and educational reports to examine current trends, benefits, and limitations of digital tools in language education. The findings reveal that technology plays a crucial role in enhancing language skills, particularly in listening, speaking, reading, and writing. Digital platforms foster interactive learning, personalized instruction, and autonomous learning experiences. However, challenges such as digital literacy gaps, accessibility issues, and the need for teacher training remain significant barriers to effective technology integration. This study concludes that while technology offers substantial benefits for English language learning, its optimal use requires strategic implementation, teacher readiness, and institutional support. Further research is needed to explore emerging technologies and their long-term impact on language acquisition.